1987
DOI: 10.1246/bcsj.60.3468
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyzed Hydrostannylation and Hydrogermylation of Acetylenes

Abstract: Treatment of acetylenes with Ph3SnH or Ph3GeH in the presence of a catalytic amount of Pd(PPh3)4 provides the corresponding alkenyltriphenylstannanes or alkenyltriphenylgermanes in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(62 citation statements)
references
References 7 publications
1
61
0
Order By: Relevance
“…[3,4] However,despite substantial progress in the development of alkyne hydrostannation catalysts,precise control over the hydrometalation regioselectivity continues to be an important challenge.S everal catalysts have now been reported that reliably provide a-vinylstannane products by catalyst-controlled hydrometalation (Scheme 1, top). [4,[12][13][14][15][16] Indeed, the only systems known to provide reasonable regioselectivities for (E)-b-vinylstannanes are highly encumbered palladium/phosphine catalysts that operate through af ormal Pd 0 /Pd II cycle. [4,[12][13][14][15][16] Indeed, the only systems known to provide reasonable regioselectivities for (E)-b-vinylstannanes are highly encumbered palladium/phosphine catalysts that operate through af ormal Pd 0 /Pd II cycle.…”
mentioning
confidence: 99%
“…[3,4] However,despite substantial progress in the development of alkyne hydrostannation catalysts,precise control over the hydrometalation regioselectivity continues to be an important challenge.S everal catalysts have now been reported that reliably provide a-vinylstannane products by catalyst-controlled hydrometalation (Scheme 1, top). [4,[12][13][14][15][16] Indeed, the only systems known to provide reasonable regioselectivities for (E)-b-vinylstannanes are highly encumbered palladium/phosphine catalysts that operate through af ormal Pd 0 /Pd II cycle. [4,[12][13][14][15][16] Indeed, the only systems known to provide reasonable regioselectivities for (E)-b-vinylstannanes are highly encumbered palladium/phosphine catalysts that operate through af ormal Pd 0 /Pd II cycle.…”
mentioning
confidence: 99%
“…Hydrogermylation of 1 with Ph 3 GeH in the presence of B(C 6 F 5 ) 3 22 in CH 2 Cl 2 at ambient temperature produced 2a in lower than 10% yields (TLC, 1 H NMR) while prolonged heating (48 h, reflux) produced a complex reaction mixture. The Pd(PPh 3 ) 4 -catalyzed hydrogermylation 19 of 1 with Ph 3 GeH in THF afforded a mixture of the expected E -isomer of 2a and the corresponding 5-[1-(triphenylgermyl)ethenyl] regioisomer, produced by addition of germyl radical to α-carbon, 19 in 3:2 ratio and 73% overall yield (entry 5; Method C). The acyl product 4a was not isolated from the reaction catalyzed by Pd(PPh 3 ) 4 .…”
mentioning
confidence: 99%
“…Palladium-catalyzed hydrogermylation of terminal acetylenes by triphenyl germane, giving E-triphenylgermyl alkenes [13], and of isoprene by tri(2-furyl)germane [14] proceeds in both cases in good yield with marked stereochemical selectivity. We reasoned that allylic germatranes might also be prepared by the germatrane hydrogermylation of the corresponding dienes, Scheme 2.…”
Section: Resultsmentioning
confidence: 99%